2015
DOI: 10.1159/000380957
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for a Pain Pathway Involving the Cingulate Gyrus: A Case of Chronic Cluster Headache Cured by Glioblastoma

Abstract: The authors report a case of a 49-year-old man with long-standing, chronic cluster headache (CH) refractory to medical therapy and occipital nerve stimulation that resolved a few weeks prior to the diagnosis of glioblastoma involving primarily the right cingulate gyrus. An attempt to explore the underlying role of the cingulate cortex in pain modulation by appraising the current literature is presented. This report suggests that the cingulate gyri could be a potential target for neuromodulation in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The cingulate gyrus is an integral part of the limbic system, which is involved with emotion formation, depression, and pain. 36 38 The limbic system is closely related to memory and emotion. 39 In the present study, we also found that patients with CS had higher ReHo values in areas in the BCG, which may suggest that strabismus has a significant changes in the limbic system.…”
Section: Discussionmentioning
confidence: 99%
“…The cingulate gyrus is an integral part of the limbic system, which is involved with emotion formation, depression, and pain. 36 38 The limbic system is closely related to memory and emotion. 39 In the present study, we also found that patients with CS had higher ReHo values in areas in the BCG, which may suggest that strabismus has a significant changes in the limbic system.…”
Section: Discussionmentioning
confidence: 99%
“…The cingulate gyrus is an essential portion of the limbic system, which plays a role in the formation of emotions 34 , depression 35 , and pain 36 . The limbic system is closely associated with memory and emotion 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The crises are serial and can last for weeks or months, associated with periods of remission that generally last for months or years. 1 2 11…”
Section: Discussionmentioning
confidence: 99%
“…Crises can last from 15 to 180 minutes, occurring one or several times a day for a few weeks, generally followed by a period of remission. 2,3 Since CH is characterized by intense, excruciating, and highly-incapacitating pain, accompanied by prominent cranial autonomic manifestations or a feeling of restlessness or agitation, it is common for CH patients to experience Palavras-chave ► cefaleia em salvas ► tratamento ► neuromodulação ► qualidade de vida ► nervo ► bloqueio anestésico…”
Section: Introductionmentioning
confidence: 99%